PENGUKURAN DAN ANALISA DATA KALIBRASI VOLTMETER DENGAN MULTI PRODUCT CALIBRATOR - Uli, R.; Delina, M.; Heryanto, B. (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
To obtain a stable electrical voltage measurements and valid, voltmeter should undergo periodic calibration with Multi Product Calibrator traceable to National Standards or International Standards. Calibration measurements performed in the DC and AC parameters on each test points ranging from the smallest to largest according to ability voltmeter. For AC voltage used in the calibration frequency setting 50Hz and 10kHz. Analysis of calibration measurements are looking for is a correction value voltmeter with Multi Product Calibrator and uncertainty (uncertainty) at each test point. The results obtained calibration Digital Multimeter 29990020 series for DC voltmeter, at least 100mV test points as correction value and its uncertainty are (-2,98x10-3) mV and ± 0,011mv, while the biggest points 250V test correction value and its uncertainty is (-0 , 0229) V and ± 0,0667V. And for AC voltmeter at the test points 10mV 50Hz smallest correction value and its uncertainty are (1,3x10-3) mV and ± 0,037mv, while at 10kHz frequency correction value and its uncertainty are (-9.9929) mV and ± 0, 0685V. For AC voltmeter at the test points 220V, 50Hz largest correction value and its uncertainty is (-0,41) V and ± 0,245V, sedangkkan at 10kHz frequency correction value and its uncertainty are (-0,235) V and ± 1,088V. Based on this calculation, it was concluded that the voltmeter still unfit for use and valid for a tiny correction value below 1V. Key words: calibration voltmeter, Multi-Product Calibrator, uncertainty of measurement.